Peran Spesialisasi Industri Auditor dalam Meningkatkan Kualitas Audit: Studi Kasus pada Kantor Akuntan Publik (KAP) Abc (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to explore the role of auditor industry specialization in improving audit quality at ABC Public Accounting Firm. Using a case study approach with an interpretive qualitative paradigm, data were collected through semi-structured interviews with three auditors who had direct experience with clients from various industry sectors. The findings indicate that auditors’ knowledge of the unique characteristics of the client’s industry plays a central role in shaping more contextual, in-depth, and responsive audit implementations. Such specialization enables auditors to identify sector-specific risks, design appropriate audit strategies, and provide added value to clients through insights that go beyond standard compliance. Furthermore, industry specialization is not merely a reflection of technical mastery but also serves as a foundation for auditors to interpret risks more accurately, enhance decision-making processes, and strengthen their professional judgment. The study highlights how industry-specific expertise fosters reflective audit practices that align with sector dynamics, thus contributing to higher audit quality and trust in financial reporting. In addition, the research emphasizes the importance of continuous learning and professional development in maintaining relevance amid evolving business environments. Overall, this study provides meaningful insight into how industry specialization enriches audit practices and reinforces the professional value of auditors within the public accounting firm environment.